SANITATION (SWACHH BHARAT MISSION), GOVERNANCE AND SOCIO-ECONOMIC DEVELOPMENT IN INDIA - Mohapatra, Amiya Kumar (European Scientific Journal, ESJ, 2015)
The degree of deprivation and socio-economic exclusion in the society can be measured by using six strategic components of human development, namely; health, basic education, nutrition, water supply, sanitation and housing. Sanitation in general and toilet facility (for households) in particular is essential for sustainable development in terms of safety, security, self-esteem and social status of the civilized society. Improved sanitation can maintain our health, the environment we live in and our quality of life and is also considered as a sign of being civilized (individual as well as country). Sanitation situation in India is quite unfortunate and distressing and thatâ€™s why urgent policy interventions are essential. â€œSwachh Bharat Missionâ€ has been introduced to address the serious issues of toilets shortage in rural as well as in urban areas. It focuses on both qualitative (usage) and quantitative (construction) improvement in sanitation in India. The biggest challenge that lies ahead is not the construction of toilets but the issue of hygiene in terms of maintenance, water supply, cleanliness. The mission tries to overcome these challenges by creating awareness among people. Besides, to ensure efficiency and effectiveness in the mission, there is need of implementing a strong monitoring mechanism that will remain vigilant in achieving the mission objectives and should evaluate output (construction) and outcomes (use) of the mission from time to time.